Drying kinetics of cupuaçu almonds cultivated in Eastern Amazon (Research, Society and Development, 2024)
In Brazil, cupuaçu (Theobroma grandiflorum Schum.) is one of the most important tropical fruits in the Amazon region. The state of Pará is the main producer in the Northern Region, with a production of 29 thousand tons. However, cupuaçu seeds go through several stages before storage, with drying being the most crucial. Therefore, the objective of this study was to analyze the drying kinetics, initial and final moisture content, drying rate, as well as fit mathematical models to experimental data to indicate the optimal temperature as a function of drying time in a prototype of a vertical fixed-bed drying silo with forced induced air, subjected to temperatures of 55°C, 65°C, and 75°C. To determine the drying kinetics, the almonds were periodically weighed until reaching equilibrium to measure the water loss. Based on the experimental drying data, moisture ratio values were determined and subsequently applied to different mathematical models. The average initial moisture content of the seeds for all temperatures was greater than 50%, while the final averages for temperatures of 55°C, 65°C, and 75°C were sequentially 13.8%, 7.25%, and 6.51%. The drying rates were 3.1%, 3.4%, and 3.8%, respectively. The modified Henderson and Pabis model provided the best fit to the experimental data. All temperatures were effective concerning the drying time. The dried almonds can be used in food manufacturing.